2004
DOI: 10.1079/bjn20041197
|View full text |Cite
|
Sign up to set email alerts
|

Greek Orthodox fasting rituals: a hidden characteristic of the Mediterranean diet of Crete

Abstract: The longevity and excellent health status of the population of Crete has been attributed to its lifestyle and dietary habits. The impact of Greek Orthodox Christian Church fasting on these dietary habits has never been studied. One hundred and twenty Greek Orthodox Christians living in Crete participated in a 1-year prospective study. One half of the subjects, who fasted regularly (fasters), and sixty non-faster controls were followed longitudinally for the three main fasting periods over 1 year; Christmas (40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
107
4
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(132 citation statements)
references
References 35 publications
15
107
4
6
Order By: Relevance
“…Our expectation that Ca intakes would be lower during the fasting week, compared with the non-fasting week, was confirmed. This is in accordance with earlier literature (9,11) and most probably reflects the restriction of dairy products during Greek Orthodox fasting periods. A finding of concern is that mean Ca intake was low during both assessment weeks.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our expectation that Ca intakes would be lower during the fasting week, compared with the non-fasting week, was confirmed. This is in accordance with earlier literature (9,11) and most probably reflects the restriction of dairy products during Greek Orthodox fasting periods. A finding of concern is that mean Ca intake was low during both assessment weeks.…”
Section: Discussionsupporting
confidence: 93%
“…In this earlier study, fish/seafood consumption also appeared to be higher whereas, in contrast to the present study, legume intake was lower when participants fasted. Meat consumption during non-fasting periods was similar to the intake reported during the non-fasting week in the present study (9) . A model of the Greek Orthodox fasting rituals was also established in another study, which assessed the nutrient composition of this eating pattern by chemically analysing the weekly food and nutrient intake of a strict adherent to the Church's recommendations (11) .…”
Section: Discussionsupporting
confidence: 89%
“…However, data on the effects of OF as practised by Orthodox monks are limited to previous studies in Orthodox monks in Crete (14)(15)(16)(17), where nutrient profiles, including energy and fat intake were more favourable during the fasting week. The monasterial state of Mount Athos in Halkidiki, Northern Greece, comprises the largest Greek monasterial community.…”
Section: Introductionmentioning
confidence: 97%
“…Whilst this diet is becoming less popular as Western-style eating habits become more widespread, Orthodox fasting (OF), a type of diet dictated by the Christian Orthodox religion, which involves periodic abstaining from certain foods, has been suggested to contribute significantly to the beneficial effects of the Mediterranean diet through a host of potentially cardio-protective mechanisms (8, 9),including the restriction of consumption of animal products and the increased consumption of plant-based foods during OF (10-12). Previous studies (13,14), reported a more favourable lipid profile and a lower body mass index (BMI) in subjects following OF compared with non-fasting controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation